PERFORMANCE ANALYSIS OF THE PUBLIC COMPANY REGIONAL DRINKING WATER TIRTA KHATULISTIWA IN PONTIANAK CITY - Alfira, Dhea; Soeryamassoeka, SB; Yulianto, Eko (Fakultas Teknik Universitas Tanjungpura, 2023)
Pontianak City's only regional public water corporation is PERUMDAM Tirta Khatulistiwa. PERUMDAM must measure its SPAM management's success as the Drinking Water Supply System (SPAM) organizer. More is needed if solely financial metrics are used to quantify PERUMDAM's SPAM management success. The BPPSPAM team, BPKP, Perpamsi, and numerous PERUMDAMs developed this performance assessment based on four performance factors: financial, service, operational, and human resources. Each part has various assessment indications to improve assessment accuracy. The performance assessment results are Healthy, Less Healthy, and Sick. PERUMDAM must be healthy to operate SPAM effectively and efficiently through internal solid management to promote drinking water coverage and quality (BPPSPAM, 2014). The company's performance was assessed by PERUMDAM Tirta Khatulistiwa utilizing KEMENDAGRI Number 47 of 1999 metrics. This examination shows that low-value firm indicators still hinder performance.This article presents research on measuring the performance of PERUMDAM Tirta Khatulistiwa Kota Pontianak for the 2021 period through an assessment of the financial aspects, service aspects, operational aspects, and human resource aspects based on the Decree of the Head of the Supporting Agency for the Development of Drinking Water Supply Systems Number 002/KPTS/K-6/IV/2010 concerning Performance Assessment of Services for the Implementation of the Development of Drinking Water Supply Systems in Drinking Water Regional Companies using the Balance Scorecard approach and making the most suitable strategy for the lowest valued assessment indicator based on performance assessment in optimizing PERUMDAM Tirta Khatulistiwa's performance using SWOT analysis.Based on the study, PERUMDAM Tirta Khatulistiwa has a total score of 3.72 for all factors; this means it is a